Realities of Watershed Management in the Philippines: The Case of the Iloilo-Maasin Watershed - Herminia A. Francisco; Jessica C. Salas (Philippine Institute for Development Studies (PIDS), 2004)
The paper analyzed the presence or absence of elements needed to have an effective system of watershed management in the Maasin Watershed, Iloilo Province. IT concluded that: a) both the legal and institutional structures needed support watershed management effort are in place; b) there is evidence of a strong social capital existing in the upland and lowland communities; c) there is an adequate level of technical capital investment to sustainably manage the watershed; and d) there is sufficient financial resources to undertake various site development initiatives. Nonetheless, with the culmination of the project, the remaining gap would be to sustain the gains already made by the stakeholders in protecting the watershed, particularly in supporting upland communities who undertake watershed protection efforts so that they will not pose a threat to the Maasin watershed. One approach put forward is to tap Environmental Service Payments.
Keywords: 330; human capital; financial capital; watershed management approach; social capital; institutional infrastructure; environmental service payments; Wasserpolitik; Wasserwirtschaft; Gewässerschutz; Nachhaltige Entwicklung; Philippinen